2011
DOI: 10.31910/rudca.v14.n1.2011.753
|View full text |Cite
|
Sign up to set email alerts
|

Integración de control biológico y de productos alternativos contra Tetranychus urticae (Acari: Tetranychidae)

Abstract: Tetranychus urticae is an important pest associated with strawberry, due to its high densities and plant damage. Farmers use acaricides in large volumes without complying with the window between the last application and harvest, resulting on toxic residues in fruits, as well as pest populations resistant to pesticides, decrement of beneficial organisms, mammalian toxicity and environmental pollution. Therefore, it is necessary to generate new alternatives for the control of this mite. The aim of this work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
1
4
0
7
Order By: Relevance
“…The results shown in Table 4 indicate that the ethanol extract of the leaves of C. aconitifolius causes a reduction in the number of eggs laid per female per day. This is consistent with the results established by Soto et al ( 2011 ), who reported that application of plant extracts may affect the oviposition of T. urticae females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results shown in Table 4 indicate that the ethanol extract of the leaves of C. aconitifolius causes a reduction in the number of eggs laid per female per day. This is consistent with the results established by Soto et al ( 2011 ), who reported that application of plant extracts may affect the oviposition of T. urticae females.…”
Section: Discussionsupporting
confidence: 93%
“…These extracts contain secondary metabolites produced by plants that have the potential to provide protection against phytophagous organisms and pathogens, and it has been found that these plant extracts also show antifungal properties (Alves 1998 ). Extracts of Cnidoscolus aconitifolius have been studied in several parts of the world, revealing lethal, sublethal and repellent effects on insects (Calderón-Montaño et al 2011 ; Ferreira and Moore 2011 ) and phytophagous mites such as T. urticae (Yoon et al 1998 ; Soto et al 2011 ; Asharaja and Sahayaraj 2013 ). Thus, as part of our research on control of economically-important pests and to generate new knowledge that can be applied by growers to manage the phytophagous mite T. urticae , the aim of this study was to determine the effect of an unfractionated ethanol-soluble extract of C. aconitifolius leaves under laboratory conditions, to provide alternative medium-term strategies to boost compliance with requirements regarding “clean products” for export.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la eficiencia de los productos alternativos para el control de plagas, así como la selectividad a enemigos naturales, está relacionada con la dosis y la formulación empleada. Es necesario tener un conocimiento técnico sobre el producto que se va a utilizar para que se obtenga un control satisfactorio de las poblaciones plaga, de manera que no afecte a los enemigos naturales asociados a estas (Soto et al, 2011).…”
Section: Resultados Y Discusiónunclassified
“…Soto et al (2010) evaluaron sobre el cultivo de fresa los productos Neem Pro®, Organic Neem® y Natuneem® para el control de T. urticae (Acari: Tetranychidae), los cuales, controlaron el 95,28% de la población siete días después de la aplicación de los mismos, sin afectar a su predador Phytoseiulus macropilis (Acari: Phytoseiidae). En otro trabajo, se evaluaron dichos productos para el control del ácaro Tetranychus evansi (Acari: Tetranychidae) en el cultivo de tomate, ocasionando el 82% de control de la población de la plaga, un día después de la aplicación (Soto et al 2011).…”
Section: Resultados Y Discusiónunclassified